Belewenis van persone na aan selfmoord slagoffers - J. Kinsella; M. Greeff; M. Poggenpoel (AOSIS, 1993)
The purpose of this study was to examine the experience of people close to suicide victims. Ten participants recited their experience through written essays, which was then analysed. Themes that were identified included a need for structure and ventilation of feelings, denial and avoidance behaviour, mixed feelings, a need to find meaning in the suicide, the development of empathy for other suffering people, impaired social relationships, and questions surrounding the suicide. These themes were used to develop a framework for supporting people close to suicide victims through general, sub-professional and professional measures.